Clinical and Radiological Outcomes of Anterior Column Reconstruction Using Titanium Mesh Cage for Dorsolumbar Spine Pathologies: Titanium Mesh Cage in Dorsolumbar Spine - Shafiq, Muhammad Danish; Shahid, Subhan; Abbas, Talha; Falak, Salman; Hameed, Muhammad Mohsin; Rimsha, .; Hameed, Abdul (Pakistan Journal of Health Sciences, 2025)
Pathological fractures in the spine, often caused by cancer, infection, or aging, can lead to vertebral compression fractures, resulting in pain, deformity, and neural compromise. Anterior cervical corpectomy with titanium mesh cages is effective for decompression, stabilization, and spinal column restoration in trauma and tumor cases. Objective: To evaluate clinical and radiological outcomes of anterior column reconstruction using cylindrical titanium mesh cage for Dorsolumbar spine pathologies. Methods: A Descriptive Case Series was conducted at the department of Neurosurgery, Fatima Jinnah Medical University/Sir Ganga Ram Hospital. 60 Patients of either gender, aged 12 to 50 years, presenting with dorsolumbar spine pathologies were included. Pre-operative and post-operative plain X-ray, MRI plain film of Spine and CT Spine (wherever required) was All surgeries were performed by a single surgeon having 10 years of post-fellowship experience. Clinical and Radiological outcomes were assessed after 3 months. The data were analyzed using SPSS version 25.0. Results: Total of 60 patients, 36.6% were in age group of 12-30 years and 63.4% were in age group of 31-50 years .There were 60% were male whereas 40% were females. Clinical outcome was excellent in 28.3%, good in 45%, fair in 23.3% and poor in 3.3%. Mean change in intervertebral space height was 1.52±0.19 and mean change in segmental angle was 0.49o ± 0.06o. Conclusion: In the current investigation it was concluded that the use of titanium mesh cages in patients with spinal disorders is safe and offering significant improvements in both clinical outcomes and radiological parameters.